International Interprofessional Collaborative Office Rounds (iiCOR): Addressing Children's Developmental, Behavioral, and Emotional Health Using Distance Technology - Kiing, Jennifer S. H.; Feldman, Heidi M.; Ladish, Chris; Srinivasan, Roopa; Donnelly, Craig L.; Chong, Shang Chee; Weitzman, Carol C. (Frontiers in Public Health, 2021)
Developmental, behavioral, and emotional issues are highly prevalent among children across the globe. Among children living in low- and middle-income countries, these conditions are leading contributors to the global burden of disease. A lack of skilled professionals limits developmental and mental health care services to affected children globally. Collaborative Office Rounds are interprofessional groups that meet regularly to discuss actual cases from the participants’ practices using a non-hierarchical, peer-mentoring approach. In 2017, International Interprofessional Collaborative Office Rounds was launched with several goals: to improve the knowledge and skills of practicing child health professionals in high and low resourced settings regarding developmental and mental health care, to support trainees and clinicians in caring for these children, and to promote best practice in diagnosis and management of these conditions. Five nodes, each comprised of 3-4 different sites with an interprofessional team, from 8 countries in North America, Africa, Asia, and South America met monthly via videoconferencing. This report describes and evaluates the first two years’ experience. Baseline surveys from participants (N=141) found that 13 disciplines were represented. Qualitative analysis of 51 discussed cases, revealed that all cases were highly complex. More than half of the cases (N=26) discussed children with autism or traits of autism and almost all (N=49) had three or more themes discussed. Frequently occurring themes included social determinants of health (N=31), psychiatric co-morbidity (N=31), aggression and self-injury (N=25), differences with the healthcare provider (N=17), cultural variation in accepting diagnosis or treatment (N=19), and guidance on gender and sexuality issues (N=8). Participants generally sought recommendations on next steps in clinical care or management. A survey of participants after year 1 (N=47) revealed that 87% (N=41) had expectations that were completely or mostly met by the program. Our experience of regular meetings of interprofessional groups from different countries using distance-learning technology allowed participants to share on overlapping challenges, meet continuing educational needs while learning about different approaches in high- and low-resourced settings. International Interprofessional Collaborative Office Rounds may prove a useful strategy for increasing the work force capacity for addressing developmental, behavioral and emotional conditions worldwide. More systematic studies are needed.